GAYA KEPEMIMPINAN KIAI DALAM MEMBANGUN SINERGITAS PESANTREN - Mashuri, Imam; Faishol, Riza; Nasrodin, Nasrodin; Fauzi, Anis (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of holding this Community Service activity is to cultivate the leadership spirit of the management of the sons and daughters' cottages with material that has been adapted to the times, as well as actual and current. In addition, it is hoped that it can move the management of the children's and daughters' cottages to develop their leadership spirit. The implementation method uses extension techniques using projectors, seminars, forum discussions and questions and answers. The results of this service activity can open the insights of the management of pondok putera and puteri about various leadership styles, so that it not only provides additional knowledge but can also be applied, especially in the management of islamic boarding schools. In addition, it can also help and increase the knowledge of the administrators of the children's and daughters' cottages related to various leadership styles of kyai today.